The Dialog in the Saltikov-Schedrin’s Novel "The Family of Golovliovs" - Dlugovskaja, Stalina (Literatūra, 1967)
The dialog in the Schedrin’s novel imparts to the narrative dramatic qualities: through the conversation character is realised. This has drawn Schedrin nearer to Tolstoy and distinguished him from Gogol and Gonscharov, who show different sides of static picture of life in the dialog, and has distinguished him from Turgenev, who shows the conversation itself: its contents, developing of its problem. But the dialog in the Schedrin’s novel is distinguished from Tolstoy’s too: it is devoid of action.The outward side of dialog (the words, gestures) disagrees with inside character’s developing. The „undercurrent" has arisen. So Schedrin anticipated some principles of the „drama without action" of Chekhov. The author of the article has tried to bound the original structure of the dialog in the Schedrin’s novel with social and psychological essence of the character (Golovliovs): the objective failure of conservative consciousness.